Dose–Response Relation between Exercise Duration and Cognition. Issue 1 (January 2015) - Chang, Yu-Kai; Chu, Chien-Heng; Wang, Chun-Chih; Wang, Yi-Chun; Song, Tai-Fen; Tsai, Chia-Liang; Etnier, Jennifer L.
ABSTRACT: Purpose: The study aimed to provide evidence-based recommendations for the prescription of a single session of exercise to improve cognitive performance. In particular, the purpose was to determine the dose–response relation between exercise duration and cognitive performance for a moderate-intensity session of aerobic exercise. Methods: Twenty-six healthy young men participated in a reading control treatment and three exercise treatments presented in a random order. The exercise treatments were designed on the basis of the American College of Sports Medicine guidelines and consisted of a 5-min warm-up, a 5-min cooldown, and cycling at moderate intensity (approximately 65% HR reserve) for 10, 20, or 45 min. The Stroop test was administrated after completion of each assigned treatment. Results: Exercise at moderate intensity for 20 min resulted in significantly better cognitive performance, as assessed by shorter response time and higher accuracy. This result was found regardless of the type of cognitive function assessed. In addition, a curvilinear dose–response relation between exercise duration and cognitive performance was observed. Conclusions: An exercise session consisting of a 5-min warm-up, 20 min of moderate-intensity exercise, and a 5-min cooldown improves cognition, whereas shorter or longer durations of moderate exercise have negligible benefits. This study provides the foundation for the prescription of a single session of moderate exercise to facilitate cognitive function in healthy younger adults.